Special Issue “Selected Papers from the 16th Weurman Flavour Research Symposium” - Elisabeth Guichard; Jean-Luc Le Quéré (Molecules, 2022)
Since 1975, the Weurman Flavour Research Symposium has been held every three years in different European countries, and has been finally established as an international event that offers unique opportunities for distinguished scientists from academia and industry, from different disciplines, and from all over the world, to discuss trends and new paradigms in the field of flavour research [...]